Large tensile plasticity in Zr-based metallic glass/stainless steel interpenetrating-phase composites prepared by high pressure die casting. (1st November 2021) - Gao, W.J.; Zhang, W.W.; Zhang, T.; Yang, C.; Huang, X.S.; Liu, Z.Y.; Wang, Z.; Li, W.H.; Li, W.R.; Li, L.; Liu, L.H.
Abstract: The ambient-temperature brittleness of bulk metallic glasses (BMGs) is a long-standing problem in materials engineering. Herein, we report a route to overcome this Achilles' heel of BMGs via high-pressure die casting (HPDC) at a high filling rate and pressure to create bi-continuous interpenetrating-phase composites. Our results show that large tensile plasticity of 5.1% can be achieved in the Zr-based BMG/stainless steel interpenetrating-phase composite prepared by HPDC, which is superior to most of as-reported ex-situ secondary phase reinforced BMG composites. The excellent mechanical properties of the BMG composite mainly originate from excellent metallurgical bonding between matrix and reinforcement as well as high efficiency suppression of shear band propagation by three-dimensional metal skeleton. Our findings provide a promising approach for developing cost-effective BMG composites suitable for industrial applications. Graphical abstract: Image 1 Highlights: Interpenetrating-phase BMG composites with large tensile plasticity were prepared successfully by high pressure die casting. The composites display metallurgical bonding between matrix and reinforcement. The excellent mechanical properties mainly originate from a proposed mutual-reinforcement mechanism. The developed process has great advantages on engineering application.